The rising costs of animal-source foods in Ethiopia: Evidence and implications - Bachewe, Fantu Nisrane; Minten, Bart; Yimer, Feiruz (International Food Policy Research Institute, 2017)
In many developing countries in which staple foods dominate the composition of diets, higher consumption of animal-source foods (ASF) is associated with significant nutritional benefits. Given the importance of prices for consumption decisions in these settings, we analyze ASF price patterns in the last decade (2007-2016), relying on a large-scale price dataset collected in 116 urban retail markets in Ethiopia. We document important seasonal and spatial patterns and we find, worryingly, that real prices of ASF have been increasing in the last decade by between 32 to 36 percent for three major ASF – milk, eggs, and meat. Similar price increases are noted in rural and urban areas and for tradable and non-tradable ASFs. This price trend is in contrast with staple cereals for which real prices stayed at similar levels over the last decade. As we estimate that a price increase of this magnitude would reduce consumption of ASF by approximately 25 percent, holding other things constant, it seems that more investments and attention to the production of ASF and the livestock sector are needed to reduce ASF prices and increase their consumption in Ethiopia.